PELATIHAN PENINGKATAN KOMPETENSI MENGENAI MODEL-MODEL PEMBELAJARAN INOVATIF BAGI PENDIDIK SEKOLAH DASAR - Merry Lapasau; Mamik Suendarti; Hasbullah Hasbullah; Virgana Virgana; Acep Musliman; Andri Suryana; Rina Hidayati Pratiwi; Fitri Damayanti; Ira Miranti (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2023)
This activity is a collaboration between the community service team of the University of Indraprasta Graduate School (Unindra) and the Centre for the Development of Educational Competence, Education and Research (P2KPTK2) in West Jakarta. Pkm activities were carried out online through zoom meetings on 1-5 August 2022 and expected to provide insight to low-level elementary school teachers in the work area of P2KPTK2 West Jakarta in terms of the use of innovative learning models in thematic learning in schools. The methods used in this activity are lectures, questions and answers and practice making educational games based on the Internet. After the community service, there is an increase in the value of the post-test results or a change between the lowest, highest, and rare values in general. At the lowest level there is a decrease of 10 points while at the highest there is no increase. The ratio increased by 32.97 points. Generally speaking, the rate of improvement in competence after the community service was 27.45%. The school is expected to provide guidance on the importance of this activity for teachers to improve competence. In addition, teachers should also be aware of the importance of improving themselves through such training to adapt to the demands of the implementation of education in the era of technology as it is now.